P2_15 Quantum well widths as a function of doping - Buccheri, Alexander; Anand, Jasdeep; Gorley, Michael; Weaver, Iain (Physics Special Topics, 2009)
We iteratively calculate theoretical data within an infinite model, that allows you to determine the required well size given a specific doping, for a laser semiconductor emitting light between the wavelengths of 450 nm and 550 nm. <span style="font-size: 11pt; font-family: ";Calibri";,";sans-serif";; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">